প্রমাণ করো, \(\bar{x}=a+h\bar{u}\) যেখানে \(\bar{x} =\cfrac{\sum f_i x_i}{\sum f_i}\) এবং \(\bar{u} =\cfrac{\sum f_i x_i}{\sum f_i}\) , \(u =\cfrac{x-a}{h}\)
আমরা জানি, \(u =\cfrac{x-a}{h}\)
অতএব, \(x = a + hu\)
বা, \(x_i = a + hu_i\)
এখন, উভয়পক্ষে \(f_i\) দিয়ে গুণ করে পাই,
\(f_i x_i = f_i (a + hu_i) = f_i a + f_i hu_i\)
\(\therefore \sum f_i x_i = \sum (f_i a + f_i hu_i)\)
\(\sum f_i x_i = \sum f_i a + \sum f_i hu_i\)
\(\sum f_i x_i = a \sum f_i + h \sum f_i u_i\) [যেহেতু \((a)\) এবং \((h)\) ধ্রুবক]
এখন উভয়পক্ষকে \(\sum f_i\) দিয়ে ভাগ করে পাই,
\(\cfrac{\sum f_i x_i}{\sum f_i} = \cfrac{a \sum f_i}{\sum f_i} + \cfrac{h \sum f_i u_i}{\sum f_i}\)
আমরা জানি, \(\bar{x} =\cfrac{\sum f_i x_i}{\sum f_i}\) এবং \(\bar{u} =\cfrac{\sum f_i u_i}{\sum f_i}\)
সুতরাং, \(\bar{x} = a + h\bar{u}\) [প্রমানিত]